THE CROWN’S FIDUCIARY DUTIES TO ABORIGINAL PEOPLES AS AN ASPECT OF CLIMATE JUSTICE - Erika Chamberlain (The Windsor Yearbook of Access to Justice, 2012)
Rapid climate change in the arctic is threatening the life, health and cultural traditions of the Inuit. Although they are among the least responsible for climate change, they are suffering disproportionately from its negative effects. In particular, the inherent link between Inuit land and culture means that their traditional practices are being threatened along with the arctic environment. However, their efforts to obtain redress from those responsible for greenhouse gas emissions have so far been unsuccessful. Claims in common law public nuisance have been plagued by issues of standing, justiciability and causation, and claims at international law are difficult to prove and enforce. It seems that a different approach may be required. This article examines whether the Crown’s fiduciary obligation toward Canada’s Aboriginal peoples might provide a useful conceptual framework for addressing arctic climate change. Although this obligation is typically applied in situations involving Aboriginal lands or distinctive cultural practices, it can arguably be invoked to protect the traditional subsistence lifestyle of the Inuit. Both the fiduciary obligations and the honour of the Crown require a minimum level of consultation and accommodation where significant Aboriginal interests are threatened. This could translate into an obligation to, at least, assist the Inuit in adapting to the changing arctic environment and preserving cultural practices to the extent possible.